A Gradient‑Boosting Model of Adolescent Social Anxiety Incorporating Rejection Sensitivity, Intolerance of Uncertainty, Emotional Reactivity, and Peer Network Centrality - Ismail, Siti Hajar; Martirosyan, Lilit; Kazak, Iryna (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to develop a highly predictive machine learning model to delineate the complex, non-linear, and synergistic contributions of rejection sensitivity, intolerance of uncertainty, emotional reactivity, and peer network centrality to adolescent social anxiety. Methods and Materials: A cross-sectional design was employed with a sample of adolescents (ages ) recruited from schools in Armenia via multistage cluster sampling. Participants completed validated Armenian translations of the Social Anxiety Scale for Adolescents (SASA), Rejection Sensitivity Questionnaire (RSQ), Intolerance of Uncertainty Scale (IUS-12), and the Emotion Reactivity Scale (ERS). Peer network centrality was quantified using eigenvector centrality scores derived from a sociometric nomination procedure. An Extreme Gradient Boosting (XGBoost) algorithm was trained and optimized using randomized search cross-validation, with model interpretability established through SHapley Additive exPlanations (SHAP). Findings: The final XGBoost model demonstrated robust predictive power on the unseen test set, explaining of the variance in social anxiety scores ( , RMSE , MAE ). Global feature importance analysis, based on mean absolute SHAP values, identified emotional reactivity as the most dominant predictor (Mean SHAP value ), followed by rejection sensitivity (Mean SHAP value ), intolerance of uncertainty (Mean SHAP value ), and peer network centrality (Mean SHAP value ). SHAP analysis further revealed significant synergistic effects, particularly between high emotional reactivity and high rejection sensitivity, which exponentially increased predicted social anxiety. Conclusion: Emotional reactivity operates as the primary driver of adolescent social anxiety, with its impact significantly amplified by concurrent cognitive and social vulnerabilities, highlighting the necessity of integrated, skills-based clinical interventions.